2024
DOI: 10.26434/chemrxiv-2024-lc1sz
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Optimal Flow and Scaling Laws for Power-Law Fluids in Elliptical Cross-Section Self-Similar Tree-Like Networks

Ashish Garg,
Himanshu Mishra,
Sudip K. Pattanayek

Abstract: Tree-like self-similar branching networks with power-law fluid flow in elliptical cross-sectional tubes are ubiquitous in nature and engineered systems. This study optimizes flow conductance within these networks under tube-volume and tube's surface-area constraints for fully developed laminar power-law fluid flow in elliptical cross-sectional tubes. We identify key network parameters influencing flow conductance and find that the efficient flow occurs when a specific ratio of the semi-major or semi-minor axis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…Additionally, maintaining the total geometrical volume of the tube within constraints is necessary to prevent the structure from becoming infinitely large. Moreover, given the expansive and limited nature of space, different parts of the system compete for available space and hence the constraint on the surface-area of the tube becomes crucial [20]. Therefore, it is essential to assess the flow resistance of the network in comparison to that of a single channel with the same length and volume or surface-area.…”
Section: Volume and Surface Area Of The Tube In Branching Networkmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, maintaining the total geometrical volume of the tube within constraints is necessary to prevent the structure from becoming infinitely large. Moreover, given the expansive and limited nature of space, different parts of the system compete for available space and hence the constraint on the surface-area of the tube becomes crucial [20]. Therefore, it is essential to assess the flow resistance of the network in comparison to that of a single channel with the same length and volume or surface-area.…”
Section: Volume and Surface Area Of The Tube In Branching Networkmentioning
confidence: 99%
“…Further applying the principle of mass conservation across a branching network and assuming that pressure losses at junctions (due to bends and contractions) are negligible compared to those along the channel lengths, the Murray's law was extended for laminar flow of non-Newtonian power-law fluids for blood in two branching channels [17,18]. These laws were further extended with arbitrary branch splitting N and power-law index n in circular and elliptical cross-sections under volume and surface-area constrained by Garg et al [19], and Garg et al [20], respectively, where they found that the optimal radius/diameter/semi-major axis length relation does not change with shear thinning/thickening power-law behaviour of fluids under volume constraint, however strongly depends on the power-law index n under surface-area constraint. Lee et al [21] introduced a theory for capillary microchannel flows within tree-like branches [21,22].…”
Section: Introductionmentioning
confidence: 99%
“…Expanding upon Murray's application of the principle of minimum work in circular tubes [25], researchers have investigated flow dynamics in tree-like branching networks. For instance, Revellin et al [26] extended Murray's law to analyze non-Newtonian power-law fluid flow in two channels, revealing a constant diameter ratio (D (k+1) /D k = 2 −1/3 ) for the optimal flow irrespective of the fluid's power-law index n. Advancements by Garg et al [1,27,28] delved into networks with varying branching numbers and power-law indices, examining circular and elliptical cross-sections under volume and surface area constraints for both laminar and turbulent flows. Notably, in the laminar flow regime, Garg et al [1,27] discovered that under volume constraints, the optimal radius/diameter/length relationship remains consistent regardless of the fluid's shear-thinning or shear-thickening behavior, denoted as (D (k+1) /D k ) * = N −1/3 .…”
Section: Introductionmentioning
confidence: 99%
“…During application, the lacquer flows through channels, tubes, and sometimes into porous materials like wood. These pores can be visualized as a simplified network of tiny channels, resembling a tree structure [13][14][15][16][17]. As the lacquer enters these pores, its flow properties, particularly viscosity and surface tension, significantly impact how it fills the network and interacts with the pore walls.…”
Section: Introductionmentioning
confidence: 99%